The secret seven - "Blyton, Enid" (Hodder Children's: London, 2002)
It's their very first adventure, and the Secret Seven super-sleuths are already on the trail of some really weird clues. Its snowing and the Seven are dressed in disguise, following a lead to a spooky old house - and a mystery